Media Education e formazione docenti: contestualizzare le esperienze videoludiche dei propri studenti - Michele Domenico Todino; Giuseppe De Simone; Stefano Di Tore (Firenze University Press, 2020)
This paper tries to find a possible link between experience, education and videogames through Dewey's book "experience and education" wrote in 1938. This American philosopher, politician and pedagogist believed that there was a fixed point in education: an "organic" link between education and personal experience; however, this link could be not be translate into a "logical syllogism": education is equal to experience. Dewey believed that it is not correct to trust that any authentic education comes automatically from experience and that all experiences are genuinely or equally educational. In this theoretical context, even videogames, like other media, could contribute to generate a positive experience "flow" in a learner, if and only if, videogames contribute to play a definable didactic-educational experience. Similarly, it is not enough for gamers to play videogames to increase skills in terms of media education or education technology. This work tries to identify characteristics that videogames should have to aim teaching-learning process.